Determination of uptake, accumulation, and stress effects in corn (Zea mays L.) grown in single-wall carbon nanotube contaminated soil. (June 2016) - Cano, Amanda M.; Kohl, Kristina; Deleon, Sabrina; Payton, Paxton; Irin, Fahmida; Saed, Mohammad; Shah, Smit Alkesh; Green, Micah J.; Cañas-Carrell, Jaclyn E.
Abstract: Single-wall carbon nanotubes (SWNTs) are projected to increase in usage across many industries. Two studies were conducted using Zea L. (corn) seeds exposed to SWNT spiked soil for 40 d. In Study 1, corn was exposed to various SWNT concentrations (0, 10, and 100 mg/kg) with different functionalities (non-functionalized, OH-functionalized, or surfactant stabilized). A microwave induced heating method was used to determine SWNTs accumulated mostly in roots (0–24 μg/g), with minimal accumulation in stems and leaves (2–10 μg/g) with a limit of detection at 0.1 μg/g. Uptake was not functional group dependent. In Study 2, corn was exposed to 10 mg/kg SWNTs (non-functionalized or COOH-functionalized) under optimally grown or water deficit conditions. Plant physiological stress was determined by the measurement of photosynthetic rate throughout Study 2. No significant differences were seen between control and SWNT treatments. Considering the amount of SWNTs accumulated in corn roots, further studies are needed to address the potential for SWNTs to enter root crop species (i.e., carrots), which could present a significant pathway for human dietary exposure. Highlights: Single-wall carbon nanotubes were taken up into corn roots, stems, leaves. A microwave induced heating method was used to detect and quantify carbon nanotubes. No significant differences were observed in photosynthetic rate among treatments.